2019
DOI: 10.1111/apt.15226
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid‐derived suppressor cells induce regulatory T cells in chronically HBV infected patients with high levels of hepatitis B surface antigen and persist after antiviral therapy

Abstract: Summary Background CD4+ regulatory T‐cells (Tregs) expand during chronic hepatitis B virus (HBV) infection and inhibit antiviral immunity, although the underlying mechanism remains largely elusive. Myeloid‐derived suppressor cells (MDSC) have been linked with T‐cell dysfunction but questions remain regarding their persistence/profile/function in chronically HBV infected patients. Aim To characterise MDSC in different phases of chronic HBV infection namely, immune‐tolerant (IT), hepatitis B e‐antigen‐positive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 44 publications
3
38
0
Order By: Relevance
“…The results revealed that MDSCs did not associate with any parameters of tumor burden and overall survival but positively correlated with several markers for hepatic injury. Evidence of our current study and previous data have shown the involvement of MDSCs in the pathogenesis of chronic HBV infection [19,20]. Taken together, compared to the role of promoting HCC progression, MDSCs seem to play a more important role in the process leading from infection to cancer.…”
Section: Discussionsupporting
confidence: 75%
“…The results revealed that MDSCs did not associate with any parameters of tumor burden and overall survival but positively correlated with several markers for hepatic injury. Evidence of our current study and previous data have shown the involvement of MDSCs in the pathogenesis of chronic HBV infection [19,20]. Taken together, compared to the role of promoting HCC progression, MDSCs seem to play a more important role in the process leading from infection to cancer.…”
Section: Discussionsupporting
confidence: 75%
“…These data partially challenge previously published data that reported robust MDSC expansion in infections and non-malignant inflammatory diseases such as psoriasis, HIV, HBV and CVDs. [23][24][25][26][27]…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in chronically HBV infected patients with high levels of HBsAg revealed the capacity of MDSCs to promote immune dysfunction through the induction of regulatory T cells, primarily via TGF-β and IL-10 dependent signaling pathways. Interestingly, a year tenofovir treatment did not result in the immune restoration of the regulatory MDSC and Treg populations (152). In addition, circulating MDSCs were significantly expanded in patients with HBV-related acute-onchronic liver failure (ACLF) and closely associated with disease progression and severity.…”
Section: Myeloid Derived Suppressor Cellsmentioning
confidence: 99%